2021
DOI: 10.3390/molecules26030677
|View full text |Cite
|
Sign up to set email alerts
|

Spirocyclic Nitroxides as Versatile Tools in Modern Natural Sciences: From Synthesis to Applications. Part I. Old and New Synthetic Approaches to Spirocyclic Nitroxyl Radicals

Abstract: Spirocyclic nitroxyl radicals (SNRs) are stable paramagnetics bearing spiro-junction at α-, β-, or γ-carbon atom of the nitroxide fragment, which is part of the heterocyclic system. Despite the fact that the first representatives of SNRs were obtained about 50 years ago, the methodology of their synthesis and their usage in chemistry and biochemical applications have begun to develop rapidly only in the last two decades. Due to the presence of spiro-function in the SNRs molecules, the latter have increased sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 215 publications
(206 reference statements)
0
11
0
Order By: Relevance
“…We now report the synthesis of bis-spiro-cyclic nitroxide radicals 1 and 2 (Figure 1) 35 and their electron spin relaxation studies in a trehalose/sucrose matrix. We find that electron spin coherence times (T m ) are significantly longer for 1 than for 2 or MTSL.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We now report the synthesis of bis-spiro-cyclic nitroxide radicals 1 and 2 (Figure 1) 35 and their electron spin relaxation studies in a trehalose/sucrose matrix. We find that electron spin coherence times (T m ) are significantly longer for 1 than for 2 or MTSL.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, the very bulky nitroxyl radical 11 was prepared and successfully applied to NMP . Spirocyclic nitroxides such as 12 , , which also belong to the sterically highly hindered N -oxyl radicals, have been prepared. The steric shielding in such spiro systems can be further increased through conformational fixation, as shown for the menthone-derived nitroxide 13 . , Other spirocyclic compounds are known, , and the bis-spiro oxetane 14 is in our eyes an interesting member of this family …”
Section: Preparation Of Nitroxides and Selected Derivativesmentioning
confidence: 99%
“…28 In spirocyclic systems, however, the lack of methyl groups significantly enhance Tm, even at higher temperatures. 29,30 Thus, the design of nitroxides for in-cell applications is often a compromise between high reduction stability and long Tm.…”
Section: Introductionmentioning
confidence: 99%
“…The conformation of spirocyclohexyl nitroxides is an important consideration: it has been proposed that such scaffolds exist as an equilibrium between open and closed conformations, where the former is preferred in solution (Figure 1B). 30 Closed conformations are, however, expected to have higher stability in reducing environments due to more effective steric shielding of the nitroxide. Previous investigations have demonstrated that disubstituted fivemembered pyrrolidinyl nitroxides (e.g.…”
Section: Introductionmentioning
confidence: 99%